2015
DOI: 10.21031/epod.14618
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’deki Araştırma Görevlilerinin Mesleki Sorunlarının İkili Karşılaştırma Yoluyla Ölçeklenmesi

Abstract: ÖzBu araştırma, araştırma görevlilerinin yaşadıkları mesleki sorunların önem düzeyini "karşılaştırmalı yargılar kanunu" kapsamında yer alan ikili karşılaştırma yoluyla ölçeklemeyi amaçlamaktadır. Bu kapsamda araştırma görevlilerinin mesleki sorunları cinsiyet, öğrenim durumu ve kadro türü değişkenlerine göre incelenmiştir. Araştırma genel tarama modeli ile desenlenmiştir. Araştırmanın örneklemini Türkiye'de Yüksek Öğretim Kurumuna bağlı devlet ve vakıf üniversitelerinde görev yapan 555 araştırma görevlisi oluş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 1 publication
0
2
0
3
Order By: Relevance
“…A pool of items for the questions to be asked to the participants were created by employing the literature about the financial incentives for scientific studies (Al, 2008;Al, 2009;Ertuna, 2014;Anıl, et al, 2015;Ulutürk, 2015;Svein & Dag, 2015;Good, et al, 2015;Andersen & Pallesen, 2008) and the Regulation on AIA (2015). The items that were found to be compatible by expert opinion were applied through the interview form to two lecturers who were not involved in the study group but who were involved in the pilot study.…”
Section: Qualitative Data Collection Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…A pool of items for the questions to be asked to the participants were created by employing the literature about the financial incentives for scientific studies (Al, 2008;Al, 2009;Ertuna, 2014;Anıl, et al, 2015;Ulutürk, 2015;Svein & Dag, 2015;Good, et al, 2015;Andersen & Pallesen, 2008) and the Regulation on AIA (2015). The items that were found to be compatible by expert opinion were applied through the interview form to two lecturers who were not involved in the study group but who were involved in the pilot study.…”
Section: Qualitative Data Collection Toolmentioning
confidence: 99%
“…Al (2008Al ( , 2009) and Ertekin (2014) have indicated that TUBITAK's Incentive Program for International Scientific Publications which were put into effect for similar purposes before Regulation on AIA, have led to an increase in the number of scientific publications. Anıl, Ertuna and Uysal (2015) suggested that research assistants should be supported by academic incentives to address their financial problems. However, even in these researches (Al, 2008;Al, 2009;Ertekin, 2014), which suggest that financial incentives will effect academicians' productivity and job satisfaction positively, it has been suggested that Turkey is in the lower rank in terms of parameters related to the quality of publications.…”
Section: Introductionmentioning
confidence: 99%
“…Akademik performansın değerlendirilmesi Akademik Teşvik Ödeneği Yönetmeliği ile daha nesnel bir hale dönüştürülmüştür. Akademik performansın doğru bir biçimde değerlendirilmesi, yükseköğretimde kalitenin objektif olarak değerlendirilmesi ve geliştirilmesi için gereklidir (Kaptanoğlu ve Özok, 2006 Araştırma görevlilerinin en önemli sorununun ekonomik problemler olması ve araştırma görevlilerinin, akademik personelin maaşlarında yapılan iyileştirmelere rağmen maddi açıdan sıkıntılar yaşamakta olduğu (Anıl, Ertuna ve Uysal, 2015) göz önüne alınırsa, akademik teşvik uygulamasıyla sağlanan maddi desteğin akademisyenlerce önemli görüldüğü göze çarpmaktadır. İşgörenlerin iş tatminin sağlanması, hem örgütün performansına hem de işgörenlerin bedensel ve psikolojik sağlığı ve motivasyonuna olumlu katkılar sağlar.…”
Section: Araştırmanın Amacıunclassified
“…Yapılan çalışmalarda da, araştırma görevlilerinin kararlara katılım ile ilgili sorunlar yaşadıkları belirtilmektedir. (29,30) Araştırmamızda akademisyen hemşireler tarafından, "kaynakların etkili dağıtımında politik kararlara katılma" maddesi en az önemli görülen maddelerden biridir. Harrington ve ark.…”
Section: Discussionunclassified